2001
DOI: 10.1152/ajpendo.2001.280.3.e528
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced muscle insulin receptor autophosphorylation with short-term aerobic exercise training

Abstract: Exercise training improves insulin action in skeletal muscle, but the mechanisms of this effect are not completely understood. In particular, the role of the insulin receptor (IR) is unclear. We examined the IR and an enzyme indicative of oxidative capacity in muscle in relation to improved insulin action in 20 previously sedentary individuals before and after a 7-day program of moderate-intensity cycle ergometry. After training, insulin sensitivity increased 33% (6.20 +/- 0.91 vs. 8.22 +/- 1.12 min. microU(-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
30
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 39 publications
6
30
0
Order By: Relevance
“…Finally, the results of the present study regarding HO-MA-IR showed that weight loss resulted in decrease in HOMA-IR, this result confirmed by Younger and colleagues reported that increased physical activity leads to improvement in insulin resistance and increase in muscle oxidative capacity which are likely contribute to the beneficial effects of exercise training on insulin action 49 . Also, Kriska and colleagues confirmed that physical activity in obese non-insulin dependent diabetes mellitus decreased blood glucose level through improving insulin sensitivity and decreasing deposition of total fat and intra-abdominal fat.…”
supporting
confidence: 89%
“…Finally, the results of the present study regarding HO-MA-IR showed that weight loss resulted in decrease in HOMA-IR, this result confirmed by Younger and colleagues reported that increased physical activity leads to improvement in insulin resistance and increase in muscle oxidative capacity which are likely contribute to the beneficial effects of exercise training on insulin action 49 . Also, Kriska and colleagues confirmed that physical activity in obese non-insulin dependent diabetes mellitus decreased blood glucose level through improving insulin sensitivity and decreasing deposition of total fat and intra-abdominal fat.…”
supporting
confidence: 89%
“…[8][9][10] In earlier studies, we have demonstrated that insulin-stimulated IR autophosphorylation is improved in muscle from subjects following a 7-day exercise training program. 31 Conversely, we have shown that high-fat feeding in rats can induce impairments in IR autophosphorylation within 2 weeks, which is before the acquisition of increased fat stores occurs. 32 In this study, we found increases in IR autophosphorylation following bariatric surgery in the four subjects with the lowest pre-surgery IR autophosphorylation.…”
Section: Discussionmentioning
confidence: 86%
“…Here we report that exercise training in Type 2 diabetic individuals resulted in a "normalization" of TG m content, but did not completely reverse insulin resistance in these patients. It is well known that endurance training improves insulin action in healthy individuals [9], with an increase in insulin sensitivity being observed after only 7 days of training [18,19,20]. The mechanisms by which exercise training improves insulin action in healthy skeletal muscle have been attributed to increases in insulin-stimulated PI3-kinase activity [18], increased expression of GLUT4 [21], hexokinase [22] and glycogen synthase [22].…”
Section: Discussionmentioning
confidence: 99%